Unlocking the therapeutic potential of Garcinia cowa Rox. in diabetes management (Sciences of Phytochemistry, 2023)
Garcinia cowa Rox. is a tropical fruit traditionally used in various parts of Asia for medicinal purposes. Recent research has indicated that it may have potential as an antidiabetic drug. Studies have shown that the extract from the fruit of G. cowa can lower blood glucose levels in diabetic rats. This effect is believed to be due to various bioactive compounds, including flavonoids and xanthones, which have demonstrated antidiabetic properties. In addition, fruit extract has also been found to improve lipid metabolism, often disrupted in individuals with diabetes. The extract has been shown to reduce levels of triglycerides, total cholesterol, and low-density lipoprotein cholesterol while increasing high-density lipoprotein cholesterol levels. Further studies are needed to explore the full potential of G. cowa as an antidiabetic drug, including clinical trials in humans. However, these initial findings suggest that this tropical fruit is a promising natural and effective treatment option for individuals with diabetes.